Left Ventricular Assist Device in the Management of Heart Failure: A Single-Center Experience - Karem, Sam; Malyala, Rajasekhar S.R.; Saha, Sibu (International Journal of Angiology, 2025)
Heart failure is a prevalent health care issue in the United States. While most cases of heart failure can be managed medically, intractable cases benefit from a left ventricular assist device (LVAD).The aim of this study is to review the outcomes of LVAD therapy at the University of Kentucky.Data received from University of Kentucky Hospital. We received Institutional Review Board approval to review patient records admitted for LVAD implantation from January 1, 2017, to December 31, 2021.After reviewing records, we had 127 eligible LVAD patients with an age range of 18 to 83 years, with 87% of recipients being white, 12.5% being black, 81% male, and 19% female. Results show the average length of admission for patients receiving LVAD is 41 days. Quality of life is reported using the New York Heart Association (NYHA) classification at follow-up, which shows 6 patients in Class I, 52 patients progressing to Class II, 21 patients to class III; other patients were deceased before discharge or did not go below class IV heart failure. Prior to 2021, there were 105 patients and 65 patients were alive at 2 years follow-up, and 18 out of 23 patients who received LVAD after 2021 are still living. For postoperative complications, 26% developed stroke, 24.4% developed gastrointestinal bleeding, 26% developed renal failure, 44.8% developed respiratory failure, 37% developed driveline infection, 14.2% developed right ventricular dysfunction/failure, and 20.4% developed an LVAD complication.LVAD has been implemented to manage advanced heart failure and improve quality of life.
Keywords: LVAD; heart failure; left ventricular assist device